Factors Affecting Acceptance of Counseling and Testing for HIVAIDS among Pregnant Women - BRAIMAH, M.E (University of Ghana, 2008)
Since Human Immunodeficiency Syndrome (HIV) detection in 1981, 25milion people have died and 65 million people are living with the disease. The HIV prevalence among antenatal care attendants rose to 40% globally with 1500 children infected each day At the end of 2007, women accounted for 50% of all adults living with HIV worldwide, and 61% in sub-Saharan Africa. In Ghana about 3,129,390 are reported living with the disease in 2007 with HIV positivity prevalence rate of 2.6% among pregnant women. Voluntary counseling and testing (VCT) have been declared the mission weapon. It is the gateway for treatment, care and support and provided free in Ghana. This study sought to examine the factors that influence the testing for HIV by pregnant women in the Ho Municipality. The study is a descriptive cross-sectional survey. It used a structured questionnaire, interview guide, Focus Group Discussion (FGD) and observations to collect data on knowledge of HIV, perception about the test and decision to test. A total of 310 antenatal women were exit interviewed in the two Prevention of Mother-To-Child (PMTCT) Centers in Ho with FGD in the communities. Majority had their sources of knowledge from radio (91.3%), Television (TV) (86.1%), “Today‟s health talk” at the clinic (81, 9%) whilst Health Workers talk (41.7%), constituted the least. They know preventive measures like abstinence, condom use and faithfulness to one‟s partner. They mentioned benefits of testing such as treatment, and knowing one‟s sero-status but only one person knew about antiretroviral therapy (ART/Prophylaxis). Less than 50% of the respondents who heard of HIV did the test. Of those who tested, age, education, religion, occupation were significantly correlated with testing in addition to the benefits that they mentioned motivated them to do it. In conclusion, the participants had universal knowledge about the modes of transmission of HIV but with misconceptions. They perceived the disease as dangerous and deadly therefore an HIV positive partner should be divorced. Stigma (77.2%), discrimination (67.1%), fear of death (86.8%) and husbands anger (51.8%) did not deter some from testing as all the men who took part in the FGD supported the test. It is recommended that Ministry of Health (MOH)/Ghana Health Service (GHS) collaborates with Ghana Education Service and the media to ensure that there is effective commitment to the policy on HIV/AIDS education and that all stakeholders are trained for empowerment.
Keywords: FACTORS; AFFECTING; ACCEPTANCE; COUNSELING; TESTING; HIV/AIDS; PREGNANT WOMEN